Staranje cevi uparjalnikov v Jedrski elektrarni Krško - Cizelj, Leon (Strojniški vestnik, 2000)
The paper reviews the domestic efforts devoted to the safe and reliable operation of the Krško nuclear power plant (NPP) at full power, close to the design limit of the steam generators (18% of plugged tubes) for a full decade. This includes an overview of the recent status and history of the degradation processes, discussion of repair criteria, defining the acceptable size of defects and selected results from safety analyses supporting the operation of degraded steam generator (SG) tubes. It is concluded that Krško NPP operated with degraded, but safe, steam generators.
Keywords: uparjalniki; Inconel 600; security; varnost; staranje; jedrska varnost; Nuklearna elektrarna Krško